Knowledge, perception and attitude about Crimean Congo Hemorrhagic Fever (CCHF) among medical and pharmacy students of Pakistan - Ali Ahmed; Maria Tanveer; Muhammad Saqlain; Gul Majid Khan (BMC, 2018)
Abstract Background Crimean Congo Hemorrhagic (CCHF) is a deadly tick born disease caused by a virus of genus Nairovirus and is endemic in the Middle East, Asia, Africa, and Eastern areas of Europe. Pakistan is a CCHF endemic country with a constant threat of sporadic outbreaks. Health care workers are more prone to CCHF, hence, it is a prerequisite for members of the healthcare team to stay abreast with current knowledge and display positive attitude and perception. This study assessed the medical and pharmacy students' preparedness level in terms of CCHF control and management. Methods A total of 900 consenting students were selected randomly, who completed a predesigned and validated questionnaire which assessed the participant's general knowledge, emergency preparedness control and management of CCHF. Data were analyzed by SPSS (IBM SPSS version 21). For data analysis percentages, P-value, t-test, the independent sample mean, Whitney U test, Kruskal-Wallis test, Logistic regression, and Spearman correlation were utilized. Results Among 900 study respondents, 68% were females and 32% were males, out of which physicians (MBBS) students were 48.4%, and pharmacists students were 51.6%. Majority of the respondents 39.9% were from age group of 22-25 years. Overall 43% healthcare students demonstrated good knowledge about disease causes, transmission, and treatment options. Additionally, 81% of the study participants showed positive attitude, whereas, 69% students demonstrated positive perceptions. The correlation coefficient showed positive correlation between attitude- perception (r = 0.268, p value = 0.000), knowledge- attitude (r = 0.234, p value = 0.000) and knowledge- perception (r = 0.257, p value = 0.000). Conclusions Knowledge gaps were observed which is alarming. These gaps were multifactorial and mainly due to lack of knowledge, poor motivation, and old syllabus which needs to be addressed. The study results show that it is crucial to evaluate current curriculum and also showing a dire need of awareness seminars, conferences workshops to highlight and educate about the current endemic disease to future health care professionals.